Human Resource Management practices in the Ghanaian Rural-Based Banking Sector. - Dwumah, Samuel (2015)
A thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (Human Resource Management Option), 2014